Total Quality Management (TQM) pada Lembaga Pendidikan Islam - Jasuri (Sekolah Tinggi Ilmu Tarbiyah (STIT) Pemalang, 2014)
Total Quality Management (TQM) is significantly implemented as an alternative solution for the improvement and quality assurance of educational institutions. Total Quality Management, also called Integrated Quality Management, is a paradigm of continuous improvement that can provide a set of practical tools to every educational institution in meeting the needs and expectations of its customers today and in the future. In the context of concerns and efforts to raise the conditions of the world of education in Indonesia in general and Islamic education in particular, there is an interesting national phenomenon which is examined by the shining of an Islamic educational institution in Indonesia. The strength of this quality management system lies in the mature, realistic and measurable planning system, and at the implementation stage it has a work pattern that refers to the best procedures chosen by the organization, while the evaluation of monitoring funds for continuous improvement is done at each stage and each line organizational processes to ensure quality for customer satisfaction. This paper tries to offer the concept of TQM to be applied to Islamic educational institutions, both formal and informal institutions.